2019
DOI: 10.1002/jmrs.336
|View full text |Cite|
|
Sign up to set email alerts
|

Association between ultrasound morphologic features and histopathological findings of lobular carcinoma

Abstract: Introduction Despite the incidence and recurrence rates of breast cancer, there are currently no biomarkers to predict which cases will develop into lobular carcinoma (LC). The purpose of this study was to determine the association between ultrasound morphologic characteristics of LC and histopathological classifications. Methods A retrospective, cross‐sectional study was conducted on the ultrasound images and histopathological reports of 100 patients with a confirmed LC diagnosis between January 2013 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Lobular tumors are also more likely to exhibit irregular contours and more diffuse margins and have a higher likelihood of satellite foci (29). We did not find a higher rate of underestimation in lobular tumors, although they made up only 10 patients of our cohort.…”
Section: Discussionmentioning
confidence: 50%
“…Lobular tumors are also more likely to exhibit irregular contours and more diffuse margins and have a higher likelihood of satellite foci (29). We did not find a higher rate of underestimation in lobular tumors, although they made up only 10 patients of our cohort.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, the morphometric features characterize the shape and contour of a lesion and are essentially independent of the system settings and machines ( 22 , 44 ). More importantly, the morphologic traits of breast cancer are associated with histological findings ( 21 , 45 , 46 ), which can provide valuable information for deriving robust multidisciplinary models ( 47 ). In this study, we found that most of the morphometric features differed significantly between benign and malignant groups, and the contributions of the selected features to the prediction model were as follows: Solidity > Circularity > Minor Axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the characteristic of shape was rare to be used as a predictive factor in BC patients because it is difficult to evaluate in surgical specimens. US is suitable to evaluate the morphometric properties of a tumor by cine clips through the masses with a longitudinal axis and a transverse axis [ 22 ]. We concluded that the US characteristic of irregular shape was a higher risk factor for the patients with short-DFS compared with a round or oval shape with an OR value of 2.052.…”
Section: Discussionmentioning
confidence: 99%